2009
DOI: 10.1186/1476-511x-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, learning behaviour and hippocampal synaptic plasticity are not disrupted in mice over-expressing the cholesterol transporter ABCG1

Abstract: BackgroundCognitive deficits are a hallmark feature of both Down Syndrome (DS) and Alzheimer's Disease (AD). Extra copies of the genes on chromosome 21 may also play an important role in the accelerated onset of AD in DS individuals. Growing evidence suggests an important function for cholesterol in the pathogenesis of AD, particularly in APP metabolism and production of Aβ peptides. The ATP-Binding Cassette-G1 (ABCG1) transporter is located on chromosome 21, and participates in the maintenance of tissue chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Another body of literature provides strong evidence that cholesterol affects both synaptic plasticity and membrane excitability of neurons in the hippocampus (Dufour et al, 2006; Fester et al, 2009; Koudinov & Koudinova, 2001; Parkinson et al, 2009; Tanaka & Sokabe, 2012; Wang & Schreurs, 2010; Ya et al, 2012). For example, Koudinov and Koudinov (2001) showed that a cholesterol diet significantly enhanced hippocampal long term potentiation, a finding that was also noted by Dufour et al (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another body of literature provides strong evidence that cholesterol affects both synaptic plasticity and membrane excitability of neurons in the hippocampus (Dufour et al, 2006; Fester et al, 2009; Koudinov & Koudinova, 2001; Parkinson et al, 2009; Tanaka & Sokabe, 2012; Wang & Schreurs, 2010; Ya et al, 2012). For example, Koudinov and Koudinov (2001) showed that a cholesterol diet significantly enhanced hippocampal long term potentiation, a finding that was also noted by Dufour et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are a significant number of reports that cholesterol modifies the electrophysiological properties of neurons in the brain particularly the hippocampus (Dufour et al, 2006; Fester et al, 2009; Koudinov & Koudinova, 2001; Parkinson et al, 2009; Tanaka & Sokabe, 2012; Wang & Schreurs, 2010; Ya et al, 2012) and, when studied in the same animals, improves spatial maze learning (Dufour et al, 2006; Ya et al, 2012). Although most of these reports have focused on synaptic plasticity (Koudinov & Koudinova, 2001; Ya et al, 2012), Wang and Schreurs (2010) have shown that a cholesterol diet also has significant effects on the membrane properties of hippocampal neurons including reductions in the size of the afterhyperpolarization – a property that has been shown to be important for learning and memory in rodents and rabbits (Bekisz et al, 2010; Disterhoft & Oh, 2006; Kaczorowski, Sametsky, Shah, Vassar, & Disterhoft, 2009; Kuiper et al, 2012; Matthews, Weible, Shah, & Disterhoft, 2008; Moyer, Jr., Thompson, & Disterhoft, 1996; Tombaugh, Rowe, & Rose, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are two studies of learning and memory in transgenic mice over-expressing ABCG1 from different groups and both failed to find any effects of ABCG1 on water maze acquisition or retention (Burgess et al ., 2008; Parkinson et al ., 2009). Perhaps like ABCA1, ABCG1 may only have an effect when learning and memory are already compromised as in the human studies of dementia and the Lefterov et al (2009) study of APP transgenic mice.…”
Section: Atp Binding Cassette Transportersmentioning
confidence: 99%
“…Cholesterol loading in vitro enhances ABCG1, but not ABCA1, expression and correlates best with cholesterol efflux from astrocytes (Karten et al, 2006). While difficult to reconcile, the in vivo and in vitro discrepancies still point to some common features: ABCG1 over-expression does not influence cognition, learning and memory, nor hippocampal synaptic plasticity (Parkinson et al, 2009), nor ABCA1 or apoE levels (Burgess et al, 2008a(Burgess et al, , 2008b in transgenic mice; suggesting a rather modest contribution of ABCG1, if any, in lipid mobilization and in the maintenance of synaptic integrity or plasticity in the adult brain.…”
Section: Discussionmentioning
confidence: 99%